UPAYA REHABILITASI LAHAN KRITIS DENGAN PENERAPAN TEKNOLOGI AGROFORESTRY SISTEM SILVOPASTORAL DI DESA OEBOLA KECAMATAN FATULEU KABUPATEN KUPANG - Matatula, Jeriels (Universitas Negeri Yogyakarta, 2009)
AbstractThe increase is a critical area of unity between the simultaneouscondition biofisik, social, economic and culture associated with the land asThe main factors of production, and implementation of policies thatconsider less sustainable. Fatuleu sub-district is one of the district with29,800 inhabitants The population, which consists of 11 villages and 1village. Livelihood of communities is 41.41% is agricultural and animalhusbandry. The goal of this activity are: 1). Rest and empowering potentialof silvopastoral agroforestry system as a source of economic income people;2). Changing the views and attitudes of farmers on land that has not beenapplying the concept of silvopastoral system; 3). Changing the system ofland use monoculture (traditional) into Multicultural (modern).Bring or change the pattern of land use monokuler need to bemultikuler process. The method is implemented with a participatoryapproach to counseling about technology silvopastoral agroforestry systemfor the rehabilitation of critical land. Demplot making model with thecondition that the land biofisik Social Economy and society, developmentdemplot plants with the implementation of silvicultural techniques thatinclude tree species selection, soil management techniques, plantingtechniques and maintenance.This activity is held on the land of farmers and the maincommodities planted on land that is provided is deplot forestry plantsnamely Mahoni with planting distance of 6 x 6 meters with the plantingholes 30x30x30 cm, while the terrace plants and Lamtoro turi.Implementation of activities or physical realization in location, the form of:1) Preparation of land for planting and seedling; 2) Making terrace; 3)Pengalian hole; 4) Planting. Planting activities have been done in the areawho have plot, but given the climate conditions of heat and rain have notbeen evenly down the steps that are taken with give irrigation teets.Key words: rehabilitation, angroforestry, and silvopastoral